The Impact of Pressure Groups on the Legislative Process - Daniel J. Dykstra (Washington University Law Quarterly, 1951)
While our society has always witnessed and even encouraged demands from its economic components, it is submitted that those who now seek to assert their influence are impelled by a sense of urgency, in truth a desperateness which at times borders on hysteria, not present in previous conflicts. Those who engineer the battles for privileges recognize that a revolutionary change in government's relation to the social economic structure has occurred and that as a consequence the stakes for which they are fighting are higher, more vital. They are cognizant in other words not only that the increased assumption of control by government makes the rewards of effective influence potentially greater, but also that this same development makes ineffectiveness potentially more costly. They accept, though reluctantly, the fact that the current position of government is not a temporary one, that it will continue to play a major, if not dominating, role in shaping our economy. For these reasons they believe that they are combatants in a battle for survival, and they fight with an intensity which in itself is evidence of the sincerity of their belief.
Keywords: Legislation